Bentuk dan Fungsi Gamelan dalam Kidung Surajaya - Binarung Mahatmajangga (Ekspresi, 2025)
AbstrakKidung Surajaya adalah naskah skriptorium Merapi-Merbabu yang bergenre santri lelana brata serta bertema kegamaan Hindu-Buddha. Teks menceritakan perjalanan Ki Singamada yang merupakan anak dari seorang penguasa di Majapahit menuju ke hutan-hutan dan pertapaan-pertapaan di pegunungan serta perjalanan spiritualnya untuk mencapai moksa. Masa penulisan teks diperkirakan berasal abad 17 Masehi di sekitar pegunungan Merapi-Merbabu sehingga dapat menjadi acuan untuk menelisik kebudayaan masyarakat Jawa pada masa itu salah satunya adalah karawitan atau gamelan Jawa. Gamelan dalam teks Kidung Surajaya ini memiliki berbagai fungsi yaitu sebagai pengiring dalam peribadatan, berkidung, peperangan, dan juga sebagai selingan pembentuk suasana keindahan dalam alur cerita Kidung Surajaya. Kata kunci: Kidung Surajaya, Karawitan, Gamelan, Manuskrip, Musik, Jawa  AbstractThe Form and Function of Gamelan in Kidung Surajaya. Kidung Surajaya is a manuscript from the Merapi-Merbabu scriptorium, categorized as a "santri lelana brata" (wandering student seeking for soul liberation) genre and featuring Hindu-Buddhist religious themes. The text narrates the journey of Ki Singamada, the son of a ruler in Majapahit, to the forests and hermitages in the mountains, as well as his spiritual journey to attain moksha (liberation). The estimated period of the text's composition is around the 17th century AD in the Merapi-Merbabu highlands, making it a reference for examining Javanese culture of that time, one aspect of which is karawitan or Javanese gamelan. The gamelan in the Kidung Surajaya text serves various functions, namely as accompaniment in worship, chanting, warfare, and also as an interlude to create an atmosphere of beauty within the storyline of the Kidung Surajaya. Keywords: Kidung Surajaya, Karawitan, Gamelan, Manuscript, Music, Java